Being Christian : exploring where you, God, and life connect - Arterburn, Stephen, 1953- (Bethany House, 2008)
"A comprehensive introduction and guide to Christianity includes core truths, information, and insights for those new to the Christian faith or curious about it, presented in a combination of narrative chapters and question/answer chapters"--Provided by publisher.